Teacher – Lecturer, or Supporting tutor?… Do and How do Teachers Check their Students’ Initial Knowledge? - Nodzyńska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
Colloquial and initial knowledge that students have is the foundation on which the teacher builds a further building of knowledge. Therefore, before starting to teach, the teacher must know what is the scope of knowledge of his students and whether their knowledge does not contain misconceptions. The article presents the results of research on over 100 high school teachers from the Małopolska voivodeship. It was examined whether and how teachers check the students’ initial knowledge. It was checked whether the teacher’s education, seniority, age, and gender have an impact on the methods used to check the students’ initial knowledge. It was also examined whether the time of checking initial knowledge by teachers was sufficient.